US Politics and Generation Y : Engaging the Millennials. - Rankin, David (Lynne Rienner Publishers, 2013)
How have the momentous events of the early 21st century affected the millennial generation's political awareness and action? What accounts for the widespread youth mobilization in support of Barack Obama during the 2008 elections? How do millennials differ from past generations in the ways that they engage in politics? Addressing these questions, David Rankin goes beyond the impact of political and cultural trends to focus on the role of higher education in connecting political interest, knowledge, and participation. Rankin draws on rich data spanning the years 2000-2010 to offer unique insigh.